Identification of the BBX gene family in blueberry at different chromosome ploidy levels and fruit development and response under stress - Yujian Xue; Jiazhuo Chen; Jia Hao; Xiaoyu Bao; Luodan Kuang; Dong Zhang; Chengwen Zong (BMC Genomics)
Abstract Background Blueberry (Vaccinium spp.) fruits are rich in flavonoids such as anthocyanins and have a high nutritional value. The zinc finger protein transcription factor B-box (BBX) plays important roles in plant growth and development, hormone response, abiotic stress, and anthocyanin accumulation. However, studies on the BBX family in blueberry are lacking. Results In total, 83 VcBBX and 24 VdBBX genes were identified in tetraploid and diploid blueberry, respectively. A correlation was observed between the number of BBX genes in blueberry and chromosome ploidy. Gene loss and specific replication during blueberry evolution may lead to an imbalance of quantitative relationship between VcBBX and VdBBX genes. The analysis of transcriptome and quantitative reverse transcription–polymerase chain reaction data revealed that the expression pattern of BBX genes depended on the developmental stage of blueberry fruit. Gibberellin inhibited the expression of most VcBBX genes. Abscisic acid promoted the expression of some members of the BBX family. The expression levels of VcBBX15b4, VcBBX21a1, and VcBBX30a in blueberry leaves were significantly downregulated under blue light treatment, whereas that of VcBBX15c3 was significantly upregulated under red light treatment. Conclusion In total, 83 VcBBX and 24 VdBBX genes were identified in 2 types of blueberries. Fruit development and transcription profiles under different stresses were analyzed. These findings will support further investigation of how BBX genes are involved in regulating hormone treatment and light stress during the growth and development of blueberry.